Study Of A Conducive And Adaptive E-Learning Environment - Asirvatham, David (2008)
The great potential of e-learning is yet to be tapped. Learners have diffrent styles of learning, diffrent pace of learning, and different preferences. With technology, it is possible to present different learning materials to different learners based on the competency level. This study will attempt to define an adaptive model for this purpose.